2021
DOI: 10.5267/j.ac.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Examining the random walk hypothesis in the Amman stock exchange: An analytical study

Abstract: The current study aimed to examine the weak-form efficiency of the Amman Stock Exchange using the weekly stock closing prices of shares for the period 2017-2019. In order to achieve the research objective, the study used the time lags that occurred between one and three weeks through the following tests: simple regression, Pearson correlation coefficient, and Spearman correlation coefficient. The study sample consisted of 179 companies. The current study concluded that the weekly stock closing prices of the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
0
5
0
6
Order By: Relevance
“…This result complements previous results on weak form efficiency conducted by Gharaibeh and Jaradat (2018), who concluded that ASE was an inefficient market in the sense that investors can use technical analysis to obtain gains in the market. In addition, in a more recent study on the same market, Obeidat et al (2020) had shown that weekly closing prices of the stocks of public joint-stock companies in ASE did not follow a random walk which conclude that the market was weak form inefficient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result complements previous results on weak form efficiency conducted by Gharaibeh and Jaradat (2018), who concluded that ASE was an inefficient market in the sense that investors can use technical analysis to obtain gains in the market. In addition, in a more recent study on the same market, Obeidat et al (2020) had shown that weekly closing prices of the stocks of public joint-stock companies in ASE did not follow a random walk which conclude that the market was weak form inefficient.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, in a more recent study on the same market, Obeidat et al (2020) had shown that weekly closing prices of the stocks of public joint-stock companies in ASE did not follow a random walk which conclude that the market was weak form inefficient. This study provides an empirical evidence that the Jordanian investor does not differ between the first time received qualification and the sequenced qualified audit report for The no reaction of investors at ASE to qualified audit reports may be attributed to: Auditors in Jordan are over-using qualified audit reports instead of make management to implement changes and corrections as required by auditors on the financial statement, as our study noted repeated qualifications over years in the same context and style.…”
Section: An Empirical Studymentioning
confidence: 97%
“…And that all of this depends on the best selection by decision makers of the appropriate analytical tools and methods for the decision problem itself. In this, (Obeidat, 2004) indicates that choosing the appropriate analytical tool depends on a number of factors associated withThe issue of the problem and the aim of addressing it and the nature of the data that was collected, as it is from the point of view of (Al-Baldawi & Al-Hamidi, 2008) that helps in making decisions in various fields with the aim of achieving the optimal use of resources, whether on the scale of the organization or the country in order to avoid the loss of capabilities on the one hand and to achieve the maximum financial return Possible investments on the other hand.…”
Section: B-tools and Methods For Analyzing Decision Alternativesmentioning
confidence: 94%
“…The sample of the main study included (40) male and female players who were deliberately chosen, because they contained enough food to conduct their main experiment. Table (1) shows a description of the characteristics of the study sample and its community steps to build the study tool:…”
Section: Methods and Proceduresmentioning
confidence: 99%